A general measles vaccination campaign in urban Guinea-Bissau: Comparing child mortality among participants and non-participants. Issue 1 (3rd January 2017) - Byberg, S.; Thysen, S.M.; Rodrigues, A.; Martins, C.; Cabral, C.; Careme, M.; Aaby, P.; Benn, C.S.; Fisker, A.B.
Highlights: Measles vaccination campaigns may reduce child mortality substantially. The reductions were greatest among girls and children already measles vaccinated. Measles vaccination campaigns may have non-specific effects. Abstract: Background: Measles vaccination campaigns targeting children aged 9–59 months are conducted every three years in Guinea-Bissau. Studies have demonstrated beneficial non-specific effects of measles vaccine. We compared mortality one year after the December 2012 measles vaccination campaign in Bissau city for children who received campaign measles vaccine with children who did not receive campaign measles vaccine. Methods: Field workers from Bandim Health Project registered all children living in the Bandim Health Project's study area who received measles vaccination at the campaign posts. Children not seen during the campaign were visited at home and campaign participation status was assessed. We compared mortality rates of participants vs. non-participants in Cox regression models. Results: 5633 children aged 9–59 months (85%) received campaign measles vaccination and 1006 (15%) did not. During the subsequent year 16 children died. Adjusted for background factors, the hazard ratio (HR) comparing measles vaccinated versus unvaccinated was 0.28 (95% CI: 0.10–0.77). The benefit was larger for girls (HR: 0.17 (0.05–0.59)) and for children who had received routine measles vaccine before the campaign (HR: 0.15 (0.04–0.63)). Conclusions: We found indications of strong beneficial non-specific effects of receiving measles vaccine during the 2012 campaign, especially for girls and children with previous routine measles vaccination. Measles vaccination campaigns may be an effective way of improving child survival.